Upaya Santri Miftahul Qiro’ah Melawan Covid-19 dengan Berkhalwat - Sarja (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
In early 2020, there was a health crisis for Indonesia. Everyone is worried about being exposed to Covid-19. It takes humility from all elements of society to hand over the handling of Covid-19 pandemic to experts in their fields, including the surrender of humans to the Creator of covid-19, namely Allah s.w.t. There are always non-scientific attitudes that must be carried out by the wider community in dealing with certain conditions (Covid-19 pandemic) as a construction of thinking to understand the pandemic. Efforts made by students at the Miftahul Qiro'ah Islamic boarding school Bojong Mengger Ciceungjing Ciamis to provide a sense of peace, calm, not panic in dealing with this condition is the seclusion approach. This study used descriptive qualitative method. Researchers went directly to the field to find out the condition of the natural object, namely the activities of the students doing seclusion at the Miftahul Qiro'ah Islamic boarding school. The results showed that in fighting COVID-19 at the Miftahul Qiro'ah Islamic boarding school, there were two approaches. First, through a spiritual approach by doing khalwat, where all students isolate themselves in the pesantren by focusing on getting closer to Allah. These activities include the meaning of non-material human values, such as truth, goodness, beauty, purity and love, spiritual, spiritual, lonely from the hustle and bustle of the world. Second, the medical approach is to follow the health protocol from the government which consists of 5M. All students wash their hands, wear masks, keep their distance, stay away from crowds, and reduce mobility.